Neuro-immune interactions in coronary microvascular disease: mechanisms and therapeutic prospect - Ge, Zhao; Wu, Guoyu; Ma, Jingguo; Ren, Silin; Liu, Tongzuo; Wu, Xudong; Wang, Xianliang (Frontiers in Immunology, 2025)
Please confirm that the below Frontiers AI generated Alt-Text is an accurate visual description of your Figure(s). These Figure Alt-text proposals won't replace your figure captions and will not be visible on your article. If you wish to make any changes, kindly provide the exact revised Alt-Text you would like to use, ensuring that the word-count remains at approximately 100 words for best accessibility results. Further information on Alt-Text can be found here.Coronary microvascular disease (CMVD) represents a widespread but frequently underdiagnosed cardiovascular condition marked by endothelial dysfunction and inflammatory microvascular remodeling. Mounting evidence underscores the pivotal involvement of neuro-immune interactions in CMVD pathogenesis, encompassing complex bidirectional communication among the autonomic nervous system, immune cells, and vascular endothelium. This review first examines the evolving paradigm of neuro-immune cardiovascular circuits and elucidates critical signaling pathways—including NF-κB, MAPK, mTOR, STAT3, and cAMP—that govern these interactions. Subsequently, to provide a clinical context for these underlying mechanisms, we present an in-depth analysis of recent clinical trials. We evaluate the evidence from large-scale cardiovascular outcome trials of anti-inflammatory agents like colchicine, alongside mechanism-based trials of vasodilators, novel cell-based therapies, and other targeted agents specifically in the CMVD population. This clinical evidence highlights the therapeutic promise of immunomodulation while underscoring the limitations of empirical, non-stratified treatment approaches. Finally, we posit that future progress depends on precision medicine frameworks that integrate neuro-immune profiling with mechanism-based patient stratification. By synthesizing contemporary mechanistic understanding and robust clinical evidence, this review advances novel diagnostic and therapeutic perspectives through a neuro-immunological lens.